Mobile Application for Productive Families Business - ALosaimi, Noura Hamad; Elzein, Nahla Mohammed; Tukka, Afaf Mohammed (IEEE, 2020)
In line with Vision 2030 KSA, to enable women economically by promoting and marketing family-made products at the lowest-cost. Moreover, Saudi productive families' projects considered as one of the main sources promote employment opportunities especially for low-income families. our project promotes self-employment by manufacturing products variety. The research aims to create a suitable-safe working environment for low-income families capable of producing goods. Furthermore, it to improve product quality through customer interaction. This search was carried out by building an Android application written in java, android studio and Firebase. In fact, we aspire to manage productive family projects with a one-application which ensures that risks are reduced while saving consumer effort with multiple options for the same product. As a result of the project's implementation low-income families market their products professionally and effectively. Also, the application allows consumers to evaluate items after receiving the service to be used for optimizations process.